2002
DOI: 10.1097/00002030-200205240-00002
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Bcl-2 and IL-2R in HIV-positive patients whose CD4 cell counts fail to increase rapidly with highly active antiretroviral therapy

Abstract: Our study characterizes the defective maintenance of peripheral CD4 T lymphocytes in CD4-LR patients, probably resulting from Bcl-2 underexpression and dysregulation of the IL-2R system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
3
7
1
1
Order By: Relevance
“…The fact that CD4 ϩ T cells from HIV-infected individuals are very sensitive to spontaneous and CD95/Fas-induced apoptosis (8), while having normal levels of Bcl-2, whereas Bcl-2 levels correlate with this apoptosis in CD8 ϩ T cells, supports this hypothesis. Our findings showing normal Bcl-2 levels in CD4 ϩ T cells differ from a previous study that showed reduced levels of Bcl-2 in CD4 ϩ T cells from HIV-infected patients (43). This discrepancy, however, may be due to differences in patient populations, as this later study focused on patients that were low responders to highly active antiretroviral therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…The fact that CD4 ϩ T cells from HIV-infected individuals are very sensitive to spontaneous and CD95/Fas-induced apoptosis (8), while having normal levels of Bcl-2, whereas Bcl-2 levels correlate with this apoptosis in CD8 ϩ T cells, supports this hypothesis. Our findings showing normal Bcl-2 levels in CD4 ϩ T cells differ from a previous study that showed reduced levels of Bcl-2 in CD4 ϩ T cells from HIV-infected patients (43). This discrepancy, however, may be due to differences in patient populations, as this later study focused on patients that were low responders to highly active antiretroviral therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…A significant inverse correlation was observed between Bak expression and the absolute numbers of CD4+ T cells in HIV-1-infected patients (Figure 2B), whereas Bax and Bim were not associated with CD4+ T cell loss in vivo (Figure 2B). As previously reported in HIV-1-infected patients [28], [30], [32], Bcl-2 was decreased in CD8+ T cells (Table 1). Ex vivo levels of Bid and FADD in CD4+ T cells and CD8+ T cells did not differ between healthy donors and HIV-1-infected individuals (Table 1).…”
Section: Resultssupporting
confidence: 86%
“…This suggests that inflammation may be driving decreased CD127 expression and inhibiting responsiveness to IL-7 and CD4 recovery in immune failure as suggested earlier by our in vitro studies where both IL-1β and IL-6 decreased CD127 expression and these cytokines as well as type 1 interferon could impair IL-7 responsiveness [18, 26]. Other studies have demonstrated that T cells from immune failure patients show reduced proliferation [11, 12] and fail to up-regulate Bcl2 [11, 12, 38] in response to IL-7. Here, we saw significantly lower proportions of Bcl2 positive CD4 T cells in immune failure, but in vitro responses to IL-7 were not examined.…”
Section: Discussionsupporting
confidence: 65%
“…Reduced levels of the pro-survival factor Bcl2 have been found in CD4 T cells from viremic HIV-infected patients [11] and immune failure patients [38], and CD4 T cells from these patients have a reduced ability to increase Bcl2 after IL-7 stimulation [11, 24]. Most CD4 T cells expressed detectable levels of Bcl2, ranging from 88%-98% in healthy controls, 89%-98% in immune success patients, and 81%-98% in immune failure patients; however the median proportion of Bcl2+ CD4 T cells was lower in immune failure patients (92%) than among healthy controls (97%, p = <0.0001) or among immune success patients (96%, p= 0.0006) (Fig.…”
Section: Resultsmentioning
confidence: 99%